Characteristics of Oxidative Storage Stability of Canola Fatty Acid Methyl Ester Stabilised with Antioxidants - Tirto Prakoso; Parncheewa Udomsap; Akiko Tanaka; Toshihiro Hirotsu; Shinichi Goto (Journal of Engineering and Technological Sciences, 2012)
The  storage  effects  on  the  oxidation  characteristics  of  fatty  acid methyl ester of canola oil (CME) were investigated  in this study.CME stabilised with  two  antioxidants, i.e.2,6-di-tert-bytyl-p-cresol  (BHT) and 6,6-di-tert-butyl-2, 2'-methylendi-p-cresol  (BPH),  was  stored at 20, 40 and  60°C.The  oxidation stability data  were measured  by  the  Rancimat test  method and  it was  found  that both BHT and BPH  addition increased  the oxidation resistance of  the  CME.  The results showed that when BPH or BHT was added at a concentration of 100 ppm, the oxidation induction period of the neat CME samples increased from 5.53 h to 6.93  hand  6.14 h,  respectively.  Comparing both antioxidants,  BPH  proved to be more  effective  in  increasing  the  oxidation  resistance  when  both  antioxidants were added at the same concentration.  Furthermore, the oxidation induction timedecreased  linearly  with  the  storage  time.  It  was  shown  that  the  oxidation occurred  rapidly  in  the  first  8  weeks  of  storage.  Later,  a  kinetic  study  was undertaken  and  first-order  kinetics  were  applied  to  explain  the  oxidation characteristics of  the  CME added with antioxidants. This kinetic study focused on  exploiting  the  activation  energy  values  obtained  from  the  Arrheniusequations. Also, the  oxidation effects on  other  quality parameters, including acid value, peroxide value, kinematic viscosity, and water content, were examined.